Increased Flood Exposure Due to Climate Change and Population Growth in the United States. Issue 11 (10th November 2020) - Swain, D. L.; Wing, O. E. J.; Bates, P. D.; Done, J. M.; Johnson, K. A.; Cameron, D. R.
Abstract: Precipitation extremes are increasing globally due to anthropogenic climate change. However, there remains uncertainty regarding impacts upon flood occurrence and subsequent population exposure. Here, we quantify changes in population exposure to flood hazard across the contiguous United States. We combine simulations from a climate model large ensemble and a high‐resolution hydrodynamic flood model—allowing us to directly assess changes across a wide range of extreme precipitation magnitudes and accumulation timescales. We report a mean increase in the 100‐year precipitation event of 20% (magnitude) and >200% (frequency) in a high warming scenario, yielding a 30–127% increase in population exposure. We further find a nonlinear increase for the most intense precipitation events—suggesting accelerating societal impacts from historically rare or unprecedented precipitation events in the 21st century. Plain Language Summary: Heavy rainfall is increasing globally due to human‐caused global warming. However, it is still unclear how these increases in heavy rainfall might affect flood risk. In this paper, we investigate how global warming and population changes together may be affecting the number of people at risk from floods in the United States. We combine simulations from a climate model and flood model—allowing us to consider a wide range of heavy rainfall events. We report a 20% increase in the size and a >200% increase in the frequency of very heavy and rare rainfall events, which leads to a 30–127% increase in the number of people at risk from floods. Finally, we find that the heaviest rainfall events increase by the widest margin—suggesting the possibility of major increases in damage and disruption caused by severe floods in the 21st century. Key Points: Population exposure to flood hazard is increasing due to both climate‐driven increases in extreme rainfall as well as demographic shifts There is a wide range of plausible increases in population exposed to flood hazard, depending strongly on climate and growth scenario We find a nonlinear increase for most extreme events, suggesting accelerating societal impacts from historically unprecedented rainfall